Effect of uniform inclined magnetic field on mixed convection in a lid-driven cavity having a horizontal porous layer saturated with a ferrofluid - Gibanov, Nikita S.; Sheremet, Mikhail A.; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Pergamon-Elsevier Science Ltd, 2017)
MHD mixed convection in a lid-driven cavity with partially filled with a porous medium saturated with a ferrofluid has been analyzed numerically. The domain of interest consists of a bottom porous layer and a nanofluid layer over the porous one with a heated motionless bottom wall and cooled upper moved wall. The governing partial differential equations formulated on the basis of a single-phase model for nano fluid, Brinkman-extended Darcy model for porous layer and Boussinesq approximation for buoyancy force have been solved by finite difference method of the second-order accuracy. Analysis has been carried out for a wide range of Hartmann number, magnetic field inclination angle, Darcy number, porous layer height, and nanoparticles volume fraction. It has been revealed that average Nusselt number is a non-monotonic function of Darcy number and porous layer height, while a growth of Hartmann number illustrates the heat transfer rate reduction. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Uniform inclined magnetic field; Mixed convection; Horizonal porous layer; Lid-driven cavity; Ferrofluid; Numerical results